INHIBIION ACTIVITY OF SOME PLANT SEEDS EXTRACTS AGAINST THE PROTEASE PRODUCED FROM LOCAL ISOLATE OF CANDIDA ALBICANS ISOLATE USING SOLID STATE FERMENTATION - N. J. SWARI,; GH. M. Aziz, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed at inhibition of purified protease produced by C. albicans using plant seeds extract. One hundred two local C. albicans isolates that were isolated and identified by microscopic and biochemical tests were submitted to primary and secondary screening techniques in order to select the qualified C. albicans isolate for protease synthesis. Among these isolates, nineteen isolates with the highest hydrolysis zone on skim milk media (primary screening) were chosen for secondary screening. It has been found that C. albicansV56 had the highest productivity of the enzyme (41.8U/mg protein). The optimum conditions of protease production by selected isolate using solid state fermentation by using wheat bran as best substrate , temperature 28 °C and pH 7, after 5 days of incubation . The enzyme was purified by concentration with sucrose, then used gel filtration chromatography using Sephadex G-75. The results show two peaks. The first peak has a purification folds 6.5 time with an enzyme yield of 13.08 %, while peak 2 has a purification folds 3.3 time with an enzyme yield of 20%. The purified enzyme exhibited maximal activity at pH 6.0 for peak 1 and 3.0 for peak 2, whereas the maximum stability was 7.0 for peak 1 and 8 for peak 2. The optimal temperature for purified enzyme activity was 40 for peak 1 and 30 for peak 2, and it was stable until 45°C. Protease activity was inhibited with local plant seed extracts. Lathyrus sativus extract inhibits approximately 50 % of protease activity.